Ye olde weird but true! : 300 outrageous facts from history - Harness, Cheryl; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2013)
Collects three hundred quirky and fun facts about history.
Includes index.
5.5
3-6
Keywords: History -- Miscellanea -- Juvenile literature; Curiosities and wonders -- Juvenile literature; History -- Miscellanea; Curiosities and wonders; History -- Miscellanea; Curiosities and wonders